ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI MOBIL MITSUBISHI PADA PT. LAUTAN BERLIAN UTAMA MOTOR BENGKULU - Hermawati Sulaiman (Creative Research Management Journal, 2018)
The purpose of this study was to determine whether design, quality and service had an effect on consumer decisions in buying Mitsubishi cars at PT. Lautan Berlian Utama Motor. In this study the methods used are quantitative analysis and qualitative analysis. The technique of sampling this study was used by accidental sampling. To facilitate the measurement of scores from the questionnaire so that the calculation is correct, then each item is given a score based on the Likert scale. From the multiple linear regression equation it was found that design (X1), quality (X2), and service (X3) had a positive influence on consumer decisions so that buying a Mitsubishi car at PT. Ocean of Berlian Utama Motor Bengkulu.